Finding the ideal strategy: Full-scale fatigue testing of wind turbine rotor shafts. Issue 7 (September 2016) - Rauert, T; Herrmann, J; Dalhoff, P; Sander, M
Abstract: For the purpose of a light weight design of rotor shafts, fatigue testing is necessary. Since full-scale fatigue tests of these large components are time consuming, costly and have not been done before, much effort has to be put into the implementation of a suitable test strategy. The paper presents the boundary conditions that have to be considered to determine the finite life regime of the component S/N-curve. A statistical simulation shows how much the derived S/N-curve is influenced by the specific test procedure.